Evaluation of resistance development and viability recovery by a non-enveloped virus after repeated cycles of aPDT - Costa, L
Nowadays, the emergence of drug resistant microorganisms is a public health concern. The antimicrobial photodynamic therapy (aPDT) has an efficient action against a wide range of microorganisms and can be viewed as an alternative approach for treating microbial infections. The aim of this study was to determine if a model target virus (T4-like bacteriophage), in the presence of the tricationic porphyrin 5,10,15-tris(1-methylpyridinium-4-yl)-20-(pentafluorophenyl)porphyrin tri-iodide (Tri-Py(+)-Me-PF), can develop resistance to aPDT and recover its viability after photodynamic treatments. To assess the development of aPDT resistance after repeated treatments, a suspension of T4-like bacteriophage was irradiated with white light (40 W m(-2)) for 120 min in the presence of 5.0 mu M of Tri-Py(+)-Me-PF (99.99% of inactivation) and new phage suspensions were produced from the surviving phages, after each cycle of light exposure. The procedure was repeated ten times. To evaluate the recovery of viral viability after photoinactivation, a suspension of T4-like bacteriophage was irradiated with white light for 120 min in the presence of 5.0 mu M of Tri-Py(+)-Me-PF on five consecutive days. In each day, an aliquot of the irradiated suspension was plated and the number of lysis plaques was counted after 24, 48, 72, 96 and 120 h of dark incubation at 37 degrees C. The profile of bacteriophage photoinactivation did not change after ten consecutive cycles and no recovery of viability was detected after five accumulated cycles of photodynamic treatment. The results suggest that aPDT represents a valuable and promising alternative therapy to treat viral infections, overcoming the problem of microbial resistance. (C) 2011 Elsevier B.V. All rights reserved.